Google Scholar: A source for clinicians? - Henderson, J. (Canadian Medical Association journal (CMAJ), 2005)
How well does Google Scholar do when it searches on medical topics? A search using "Vioxx" generated links to older research articles, with nothing on the drug's withdrawal from the market in the first pages of citations (the searches for this article were conducted in April 2005). The first hit generated by a Scholar search on "C-reactive protein" was an important article published in 2000 in the New England Journal of Medicine, but the next 100 hits showed only 9 articles from 2003 and 2004, and none from 2005. "Medicine" limited to 2005 publications resulted in 12 hits. However, a search on the "BODE index" for chronic obstructive pulmonary disease did lead to key 2004 citations. Searches on "cognitive behavioural therapy" and "cognitive behavioral therapy" produced quite different results. There are other shortcomings. Because results emphasize pages that are cited more often, this creates a bias toward older literature. Many medical links found in both Google and Google Scholar are from PubMed (ncbi.nlm.nih.gov in search results); however, Scholar accesses only 1 million of the some 15 million records at PubMed.3 Although it enables citation searching, Scholar does not offer a "similar pages" feature as Google does to find pages on the same subject. Nor does it offer Google's "Did you mean" feature, which addresses spelling mistakes and variations by providing alternates. The only major health database used is MEDLINE, which means that the "deep" Web stored in databases that index the journal literature, such as Excerpta Medica, CINAHL (Cumulative Index to Nursing and Allied Health Literature), and PsycInfo, remains difficult to access. These shortcomings make Scholar, for now, a supplementary tool for clinicians at best.